Hybrid liquid biphasic system for cell disruption and simultaneous lipid extraction from microalgae Chlorella sorokiniana CY-1 for biofuel production - Yew G.Y.; Chew K.W.; Malek M.A.; Ho Y.-C.; Chen W.-H.; Ling T.C.; Show P.L. (BioMed Central Ltd., 2023)
Biofuels; Cells; Chemical analysis; Cytology; Extraction; Lipids; Microorganisms; Organic solvents; Bi-phasic solutions; Biofuels production; Chemical pre-treatment; Chlorella sorokiniana; Liquid biphasic systems; Micro-algae; Pretreatment process; Radical; Algae; biofuel; concentration (composition); diesel; lipid; liquid; microalga; performance assessment; solvent; Chlorella sorokiniana